Anti-skid and anti-aging swimming pool adhesive film and preparation method thereof

By combining modified polyvinyl chloride and loaded metal ion zinc oxide filler, a swimming pool film with a cross-linked network structure is formed, which solves the problems of pool film aging and chlorinated disinfectant corrosion, improves aging resistance and anti-slip performance, and It achieves the effect of water quality safety and reducing maintenance costs.

CN119193024AInactive Publication Date: 2024-12-27LANDY GUANGZHOU PLASTIC PROD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411219214.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing swimming pool film ages under long-term ultraviolet irradiation, the materials discolor and embrittle, and chlorinated disinfectants cause corrosiveness to PVC, affecting service life and water quality safety.

Method used

Using modified polyvinyl chloride, zinc oxide filler with metal ions, diisononyl cyclohexane-1,2-dicarboxylate, dioctyl adipic acid, paraffin oil, barium zinc liquid stabilizer and phosphite The swimming pool film composed of the same is composed of physical mixing and injection molding to form a cross-linking network structure, improving aging resistance and anti-slip performance, and reducing the use of chlorinated disinfectants through the sustained release bactericidal effect of zinc oxide.

Benefits of technology

It significantly improves the aging resistance, anti-slip properties and water quality safety of the swimming pool film, extends the service life, reduces maintenance costs, and achieves a slow release and sterilization effect under light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005022495340000101
    Figure BDA0005022495340000101
  • Figure BDA0005022495340000102
    Figure BDA0005022495340000102
  • Figure BDA0005022495340000111
    Figure BDA0005022495340000111
Patent Text Reader

Abstract

The invention provides an anti-skid and anti-aging swimming pool adhesive film and a preparation method thereof, and belongs to the technical field of swimming pool adhesive films. The swimming pool adhesive film is prepared from modified polyvinyl chloride, filler, cyclohexane-1, 2-dicarboxylic acid diisononyl ester, dioctyl adipate, paraffin oil, a barium-zinc liquid stabilizer, phosphite ester and organic pigment, and the filler is modified zinc oxide loaded with multiple metal ions; through mutual cooperation and synergistic effects of the components, the prepared swimming pool adhesive film has good mechanical properties, aging resistance and the like, can achieve slow-release sterilization effects indoors and under illumination, reduces use of a chlorinated disinfectant, improves water quality safety, reduces swimming pool maintenance cost, and is beneficial to application of a polyvinyl chloride material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of swimming pool adhesive films, and in particular to an anti-skid and aging-resistant swimming pool adhesive film and a preparation method thereof. Background Art

[0002] Pool film is a waterproof decorative material used for the inner wall of swimming pools. It has gradually become a substitute for ceramic tiles and mosaics due to its durability, easy installation and simple maintenance. This material is usually made of PVC (polyvinyl chloride), has good waterproof performance and decorative effect, and can be used not only for indoor swimming pools but also for outdoor swimming pools. However, PVC is prone to aging under long-term ultraviolet radiation, causing discoloration and embrittlement of the material, thus affecting its service life and aesthetics, limiting its application in swimming pool construction.

[0003] Existing swimming pool disinfection generally uses chlorinated disinfectants, which kill bacteria and viruses by reacting with water to produce hypochlorous acid. These substances are also corrosive to PVC, and swimmers who are exposed to chlorine-containing disinfectants for a long time may increase the risk of asthma, bronchial hyperreactivity and respiratory inflammation.

[0004] Based on this, it is urgent to develop a new swimming pool film. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a non-slip and aging-resistant swimming pool film and a preparation method thereof.

[0006] In order to achieve the above purpose, the present invention solves the technical problem by adopting the following technical solutions:

[0007] On the one hand, the present invention provides a non-slip and aging-resistant swimming pool film, which comprises, by mass, 40-70 parts of modified polyvinyl chloride, 4-15 parts of filler, 1-8 parts of cyclohexane-1,2-diisononyl dicarboxylate, 8-15 parts of dioctyl adipate, 1-5 parts of paraffin oil, 0.5-4 parts of barium zinc liquid stabilizer, 0.1-3 parts of phosphite, and 0.5-2 parts of organic pigment;

[0008] Wherein, the filler is zinc oxide loaded with metal ions.

[0009] Preferably, in parts by mass, it includes 50-60 parts of modified polyvinyl chloride, 8-12 parts of filler, 2-7 parts of diisononyl cyclohexane-1,2-dicarboxylate, 10-12 parts of dioctyl adipate, 2-3 parts of paraffin oil, 1-3 parts of barium zinc liquid stabilizer, 0.5-2 parts of phosphite, and 1.2-1.5 parts of organic pigment.

[0010] Preferably, in parts by mass, it includes 55 parts of modified polyvinyl chloride, 10 parts of filler, 5 parts of diisononyl cyclohexane-1,2-dicarboxylate, 11 parts of dioctyl adipate, 2.5 parts of paraffin oil, 2 parts of barium zinc liquid stabilizer, 1 part of phosphite, and 1.3 parts of organic pigment.

[0011] Preferably, the average degree of polymerization of the polyvinyl chloride is 980-1080.

[0012] Preferably, the preparation of the modified polyvinyl chloride comprises the following steps:

[0013] Under a protective atmosphere, polyvinyl chloride resin powder, 2-allyl-4-methylphenol and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then the temperature is raised to 70-80°C and kept for 1-3 hours, then the temperature is raised to 110-130°C and mechanically stirred for 30 minutes to obtain a mixture, deionized water is added at a material-liquid ratio of 1:(10-30) and the mixture is reacted at 110-130°C for 4-8 hours, filtered and dried to obtain modified polyvinyl chloride.

[0014] Preferably, the added amount of the 2-allyl-4-methylphenol is 3-7wt% of the polyvinyl chloride resin powder, and the added amount of the dibenzoyl peroxide is 0.3-0.5wt% of the polyvinyl chloride resin powder.

[0015] Preferably, the preparation of the filler comprises the following steps:

[0016] S1. Add zinc oxide with a particle size of 1 μm into anhydrous ethanol and stir to disperse for 1 hour, then add vinyltrimethoxysilane solution, heat to 65-75°C and react for 4-8 hours. After the reaction is completed, cool to room temperature, wash with anhydrous ethanol, and dry to obtain modified zinc oxide.

[0017] S2. Use ultrapure water to prepare 0.6-1 mol / L silver nitrate solution and 0.8-1.2 mol / L copper nitrate solution respectively, then mix the silver nitrate solution and the copper nitrate solution in a volume ratio of 1:2, and stir at 300-500 rpm for 30 minutes to obtain a metal precursor solution.

[0018] S3. Immerse the modified zinc oxide in the metal precursor solution, stir continuously at 65-75° C. for 4-6 hours, and then dry to obtain a filler loaded with metal ions.

[0019] Preferably, the vinyltrimethoxysilane solution is prepared by mixing vinyltrimethoxysilane, anhydrous ethanol and ultrapure water in a mass ratio of (0.5-1.5):12:12.

[0020] Preferably, the filler is in the shape of a layer or a sheet.

[0021] Preferably, the preparation of the swimming pool film includes:

[0022] After mixing the components, physical kneading is performed at a temperature of 190-210°C, a rotation speed of 400-500rpm, and a kneading time of 20-40min; after kneading, it is molded by an injection molding machine at an injection molding temperature of 160-200°C, a mold room temperature, an injection molding pressure of 500-700bar, and an injection molding time of 10-20s. After the injection molding is completed, the pressure is maintained at 500-70bar, and the swimming pool film is obtained through embossing, cooling, and trimming.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention provides a new swimming pool adhesive film, comprising modified polyvinyl chloride, filler, diisononyl cyclohexane-1,2-dicarboxylate, dioctyl adipate, paraffin oil, barium zinc liquid stabilizer, phosphite, and organic pigment; wherein the modified polyvinyl chloride is prepared by thermally decomposing dibenzoyl oxide to produce strong free radicals, followed by grafting 2-allyl-4-methylphenol, and introducing a hindered phenol structure, thereby providing an overall composite material with improved aging resistance.

[0025] At the same time, the present invention also modifies the surface of zinc oxide by organic silicon to obtain zinc oxide containing double bonds, which further improves the anti-aging effect, can also be cross-linked with the main body to form a cross-linked network structure, and improves the stability and mechanical properties of the overall material. In addition, the zinc oxide particle size is relatively large, and after the film is prepared, the surface of the overall material is uneven, thereby increasing the anti-slip property. In addition, the zinc oxide can slowly release zinc ions and synergize with the loaded metal ions to achieve a slow-release sterilization effect both indoors and under light, thereby reducing the use of chlorinated disinfectants, improving water quality safety, and reducing the maintenance cost of the swimming pool.

[0026] In addition, the preparation method of the present invention is simple and can be used for large-scale industrial production, which promotes the development of polyvinyl chloride materials and provides new ideas for swimming pool materials. DETAILED DESCRIPTION

[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0029] Example 1

[0030] 1. A non-slip and aging-resistant swimming pool film, comprising, by mass, 55 parts of modified polyvinyl chloride, 10 parts of filler, 5 parts of diisononyl cyclohexane-1,2-dicarboxylate, 11 parts of dioctyl adipate, 2.5 parts of paraffin oil, 2 parts of barium zinc liquid stabilizer, 1 part of phosphite, and 1.3 parts of organic pigment.

[0031] 2. The preparation of the swimming pool film comprises the following steps:

[0032] 1. Graft modification of polyvinyl chloride:

[0033] In a nitrogen atmosphere, polyvinyl chloride resin powder (average degree of polymerization of 980-1080), 2-allyl-4-methylphenol, and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then heated to 75°C for 2 hours, then heated to 120°C for mechanical stirring for 30 minutes to obtain a mixture, then deionized water is added at a material-liquid ratio of 1:20 and reacted at 120°C for 6 hours, filtered and dried to obtain modified polyvinyl chloride. The amount of 2-allyl-4-methylphenol added is 5wt% of the polyvinyl chloride resin powder, and the amount of dibenzoyl peroxide added is 0.4wt% of the polyvinyl chloride resin powder.

[0034] 2. Preparation of filler:

[0035] (1) Weigh 50 g of zinc oxide (purity 99.9%) with a particle size of 1 μm, add it to 150 mL of anhydrous ethanol, stir and disperse it for 1 h, then add 200 mL of vinyl trimethoxysilane solution (prepared by mixing vinyl trimethoxysilane, anhydrous ethanol and ultrapure water in a mass ratio of 1:12:12), heat it to 70° C. at 2° C. / min and react for 6 h. After the reaction is completed, cool it to room temperature, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 50° C. overnight to obtain modified zinc oxide.

[0036] (2) Preparation of metal precursor solution: Use ultrapure water to prepare 0.8 mol / L silver nitrate solution and 1 mol / L copper nitrate solution respectively, then mix the silver nitrate solution and the copper nitrate solution in a volume ratio of 1:2, and stir at 400 rpm for 30 min.

[0037] (3) The modified zinc oxide is immersed in a metal precursor solution, stirred continuously at 70° C. for 5 hours, and then dried to obtain the modified zinc oxide loaded with metal particles, i.e., the loaded filler.

[0038] 3. After mixing the raw materials according to the above mass parts, they were physically mixed in a torque rheometer at a temperature of 200°C, a rotation speed of 450rpm, and a mixing time of 30min; after mixing, they were molded by an injection molding machine at an injection molding temperature of 180°C, a mold room temperature, an injection molding pressure of 600bar, and an injection molding time of 15s. After the injection molding was completed, the pressure was maintained at 600bar, and the swimming pool film was obtained by embossing, cooling, and trimming.

[0039] Example 2

[0040] 1. A non-slip and aging-resistant swimming pool film, comprising, by mass, 50 parts of modified polyvinyl chloride, 12 parts of filler, 7 parts of cyclohexane-1,2-diisononyl dicarboxylate, 10 parts of dioctyl adipate, 3 parts of paraffin oil, 1 part of barium zinc liquid stabilizer, 2 parts of phosphite, and 1.2 parts of organic pigment.

[0041] 2. The preparation of the swimming pool film comprises the following steps:

[0042] 1. Graft modification of polyvinyl chloride:

[0043] In a nitrogen atmosphere, polyvinyl chloride resin powder (average degree of polymerization of 980-1080), 2-allyl-4-methylphenol, and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then heated to 70°C for 3 hours, then heated to 130°C for mechanical stirring for 30 minutes to obtain a mixture, then deionized water is added at a material-liquid ratio of 1:10 and reacted at 110°C for 4 hours, filtered and dried to obtain modified polyvinyl chloride. The addition amount of the 2-allyl-4-methylphenol is 3wt% of the polyvinyl chloride resin powder, and the addition amount of the dibenzoyl peroxide is 0.5wt% of the polyvinyl chloride resin powder.

[0044] 2. Preparation of filler:

[0045] (1) Weigh 50 g of zinc oxide (purity 99.9%) with a particle size of 1 μm, add it to 150 mL of anhydrous ethanol, stir and disperse it for 1 h, then add 200 mL of vinyl trimethoxy silane solution (prepared by mixing vinyl trimethoxy silane, anhydrous ethanol and ultrapure water in a mass ratio of 0.5:12:12), heat it to 65° C. at 2° C. / min and react for 8 h. After the reaction is completed, cool it to room temperature, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 50° C. overnight to obtain modified zinc oxide.

[0046] (2) Preparation of metal precursor solution: Use ultrapure water to prepare 0.6 mol / L silver nitrate solution and 1.2 mol / L copper nitrate solution respectively, then mix the silver nitrate solution and the copper nitrate solution in a volume ratio of 1:2, and stir at 400 rpm for 30 min.

[0047] (3) The modified zinc oxide is immersed in a metal precursor solution, stirred continuously at 65° C. for 6 hours, and then dried to obtain the modified zinc oxide loaded with metal particles, i.e., the loaded filler.

[0048] 3. The raw materials were mixed according to the above mass parts and then physically mixed in a torque rheometer at a temperature of 190°C, a rotation speed of 400 rpm, and a mixing time of 40 min. After mixing, the mixture was formed by an injection molding machine at an injection molding temperature of 180°C, a mold room temperature, an injection molding pressure of 600 bar, and an injection molding time of 15 s. After the injection molding was completed, the pressure was maintained at 600 bar, and the swimming pool film was obtained by embossing, cooling, and trimming.

[0049] Example 3

[0050] A non-slip and aging-resistant swimming pool film comprises, by mass, 60 parts of modified polyvinyl chloride, 8 parts of filler, 2 parts of cyclohexane-1,2-diisononyl dicarboxylate, 12 parts of dioctyl adipate, 2 parts of paraffin oil, 3 parts of barium zinc liquid stabilizer, 0.5 parts of phosphite, and 1.5 parts of organic pigment.

[0051] 2. The preparation of the swimming pool film comprises the following steps:

[0052] 1. Graft modification of polyvinyl chloride:

[0053] In a nitrogen atmosphere, polyvinyl chloride resin powder (average degree of polymerization of 980-1080), 2-allyl-4-methylphenol, and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then heated to 80°C for 1 hour, then heated to 110°C for mechanical stirring for 30 minutes to obtain a mixture, then deionized water is added at a material-liquid ratio of 1:30 and reacted at 130°C for 8 hours, filtered and dried to obtain modified polyvinyl chloride. The amount of 2-allyl-4-methylphenol added is 7wt% of the polyvinyl chloride resin powder, and the amount of dibenzoyl peroxide added is 0.3wt% of the polyvinyl chloride resin powder.

[0054] 2. Preparation of filler:

[0055] (1) Weigh 50 g of zinc oxide (purity 99.9%) with a particle size of 1 μm, add it to 150 mL of anhydrous ethanol, stir and disperse it for 1 h, then add 200 mL of vinyl trimethoxy silane solution (prepared by mixing vinyl trimethoxy silane, anhydrous ethanol and ultrapure water in a mass ratio of 1.5:12:12), heat it to 75° C. at 2° C. / min and react for 4 h. After the reaction is completed, cool it to room temperature, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 50° C. overnight to obtain modified zinc oxide.

[0056] (2) Preparation of metal precursor solution: Use ultrapure water to prepare 1 mol / L silver nitrate solution and 0.8 mol / L copper nitrate solution respectively, then mix the silver nitrate solution and the copper nitrate solution in a volume ratio of 1:2, and stir at 400 rpm for 30 min.

[0057] (3) The modified zinc oxide is immersed in a metal precursor solution, stirred continuously at 75° C. for 4 hours, and then dried to obtain the modified zinc oxide loaded with metal particles, i.e., the loaded filler.

[0058] 3. After mixing the raw materials according to the above mass parts, they were physically mixed in a torque rheometer at a temperature of 210°C, a rotation speed of 500 rpm, and a mixing time of 20 min; after mixing, they were molded by an injection molding machine at an injection molding temperature of 180°C, a mold room temperature, an injection molding pressure of 600 bar, and an injection molding time of 15 s. After the injection molding was completed, the pressure was maintained at 600 bar, and the swimming pool film was obtained by embossing, cooling, and trimming.

[0059] Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that the components of the swimming pool film are different, and the other components are the same.

[0061] In parts by mass, the swimming pool film includes 30 parts of modified polyvinyl chloride, 20 parts of filler, 10 parts of diisononyl cyclohexane-1,2-dicarboxylate, 5 parts of dioctyl adipate, 8 parts of paraffin oil, 5 parts of barium zinc liquid stabilizer, 5 parts of phosphite, and 1.3 parts of organic pigment.

[0062] Comparative Example 2

[0063] The difference between Comparative Example 2 and Example 1 is that the components of the swimming pool film are different, and the other components are the same.

[0064] In parts by mass, the swimming pool film includes 80 parts of modified polyvinyl chloride, 3 parts of filler, 1 part of diisononyl cyclohexane-1,2-dicarboxylate, 20 parts of dioctyl adipate, 1 part of paraffin oil, 0.5 parts of barium zinc liquid stabilizer, 0.1 parts of phosphite, and 1.3 parts of organic pigment.

[0065] Comparative Example 3

[0066] The difference between Comparative Example 3 and Example 1 is that the modified polyvinyl chloride is replaced by commercially available polyvinyl chloride resin powder of equal mass (average degree of polymerization of 980-1080), and the other conditions are the same.

[0067] Comparative Example 4

[0068] The difference between Comparative Example 4 and Example 1 is that the filler is replaced by an equal mass of light calcium carbonate, and the other contents are the same.

[0069] Comparative Example 5

[0070] The difference between Comparative Example 5 and Example 1 is that the graft modification of the polyvinyl chloride is different, and the others are the same.

[0071] In a nitrogen atmosphere, polyvinyl chloride resin powder (average degree of polymerization of 980-1080), methyl methacrylate, and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then heated to 60°C for 2 hours, then heated to 150°C for mechanical stirring for 30 minutes to obtain a mixture, then deionized water is added at a material-liquid ratio of 1:8 and reacted at 100°C for 6 hours, filtered and dried to obtain modified polyvinyl chloride. The amount of methyl methacrylate added is 2wt% of the polyvinyl chloride resin powder, and the amount of dibenzoyl peroxide added is 0.2wt% of the polyvinyl chloride resin powder.

[0072] Comparative Example 6

[0073] The difference between Comparative Example 6 and Example 1 is that the modified zinc oxide is different, and the other aspects are the same.

[0074] Weigh 50 g of zinc oxide with a particle size of 1 μm (purity 99.9%), add it to 150 mL of anhydrous ethanol and stir and disperse it for 1 h, then add 200 mL of γ-aminopropyltriethoxysilane solution (prepared by mixing γ-aminopropyltriethoxysilane, anhydrous ethanol, and ultrapure water in a mass ratio of 0.1:4:4), heat to 60°C at 2°C / min and react for 2 h. After the reaction is completed, cool to room temperature, wash with anhydrous ethanol, and dry in a vacuum drying oven at 50°C overnight to obtain modified zinc oxide.

[0075] Test Example 1

[0076] The swimming pool films prepared in Examples 1-3 and Comparative Examples 1-6 were cut into 3mm×3mm×0.5mm sheets as test samples, and the performance tests were performed on the test samples according to the national standard GB / T28935-2012 "Disassembly-type swimming pools". The antibacterial test was performed according to JIS Z 2801 "2010 Antibacterial processed products - Antibacterial test methods, antibacterial effects". The anti-aging performance retention rate calculation formula is as follows:

[0077]

[0078] Table 1 Mechanical properties test table of swimming pool film

[0079]

[0080]

[0081] Table 2 Test results of anti-penetration, temperature stability and light stability of swimming pool film

[0082]

[0083]

[0084] As shown in Table 1-2, compared with Comparative Examples 1-6, the swimming pool film prepared in Examples 1-3 has good mechanical properties, and the elongation at break can reach more than 200%. At the same time, it also has good anti-permeability, temperature stability and light stability, which is beneficial to the application of swimming pool film. In particular, it can be seen from Comparative Examples 3, 5 and Example 1 that the modified polyvinyl chloride can significantly improve the aging resistance of the overall material. At the same time, it can be seen from Comparative Examples 4, 6 and Example 1 that compared with inorganic fillers such as light calcium carbonate, the filler of the present invention can not only further improve the aging resistance of the overall material by modifying zinc oxide with double bonds and loading multiple metal ions, but also zinc oxide can slowly release zinc ions under light, and synergistically with other metal ions, which is beneficial to improve the antibacterial property of the overall material.

[0085] It can be seen from Comparative Examples 1-2 that only when modified polyvinyl chloride, filler, diisononyl cyclohexane-1,2-dicarboxylate, dioctyl adipate, paraffin oil, barium zinc liquid stabilizer, phosphite, organic pigment and preparation method cooperate and coordinate with each other within a certain range, the obtained swimming pool film has better performance.

[0086] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A non-slip and aging-resistant swimming pool film, characterized in that: In parts by mass, it comprises 40-70 parts of modified polyvinyl chloride, 4-15 parts of filler, 1-8 parts of diisononyl cyclohexane-1,2-dicarboxylate, 8-15 parts of dioctyl adipate, 1-5 parts of paraffin oil, 0.5-4 parts of barium zinc liquid stabilizer, 0.1-3 parts of phosphite, and 0.5-2 parts of organic pigment; Wherein, the filler is zinc oxide loaded with metal ions.

2. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: In parts by mass, it includes 50-60 parts of modified polyvinyl chloride, 8-12 parts of filler, 2-7 parts of diisononyl cyclohexane-1,2-dicarboxylate, 10-12 parts of dioctyl adipate, 2-3 parts of paraffin oil, 1-3 parts of barium zinc liquid stabilizer, 0.5-2 parts of phosphite, and 1.2-1.5 parts of organic pigment.

3. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: In parts by mass, it includes 55 parts of modified polyvinyl chloride, 10 parts of filler, 5 parts of diisononyl cyclohexane-1,2-dicarboxylate, 11 parts of dioctyl adipate, 2.5 parts of paraffin oil, 2 parts of barium zinc liquid stabilizer, 1 part of phosphite, and 1.3 parts of organic pigment.

4. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: The average polymerization degree of the polyvinyl chloride is 980-1080.

5. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: The preparation of the modified polyvinyl chloride comprises the following steps: Under a protective atmosphere, polyvinyl chloride resin powder, 2-allyl-4-methylphenol and dibenzoyl peroxide are added to a reaction kettle and stirred evenly, then the temperature is raised to 70-80°C and kept for 1-3 hours, then the temperature is raised to 110-130°C and mechanically stirred for 30 minutes to obtain a mixture, deionized water is added at a material-liquid ratio of 1:(10-30) and the mixture is reacted at 110-130°C for 4-8 hours, filtered and dried to obtain modified polyvinyl chloride.

6. The anti-skid and aging-resistant swimming pool film according to claim 5, characterized in that: The added amount of the 2-allyl-4-methylphenol is 3-7wt% of the polyvinyl chloride resin powder, and the added amount of the dibenzoyl peroxide is 0.3-0.5wt% of the polyvinyl chloride resin powder.

7. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: The preparation of the filler comprises the following steps: S1. Add zinc oxide with a particle size of 1 μm into anhydrous ethanol and stir to disperse for 1 hour, then add vinyltrimethoxysilane solution, heat to 65-75°C and react for 4-8 hours. After the reaction is completed, cool to room temperature, wash with anhydrous ethanol, and dry to obtain modified zinc oxide. S2. Use ultrapure water to prepare 0.6-1 mol / L silver nitrate solution and 0.8-1.2 mol / L copper nitrate solution respectively, then mix the silver nitrate solution and the copper nitrate solution in a volume ratio of 1:2, and stir at 300-500 rpm for 30 minutes to obtain a metal precursor solution. S3. Immerse the modified zinc oxide in the metal precursor solution, stir continuously at 65-75° C. for 4-6 hours, and then dry to obtain a filler loaded with metal ions.

8. The anti-skid and anti-aging swimming pool film according to claim 7, characterized in that: The vinyltrimethoxysilane solution is prepared by mixing vinyltrimethoxysilane, anhydrous ethanol and ultrapure water in a mass ratio of (0.5-1.5):12:

12.

9. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: The filler can be in the form of layers, sheets or particles.

10. The anti-skid and aging-resistant swimming pool film according to claim 1, characterized in that: The preparation of the swimming pool film comprises: After mixing the components, physical kneading is performed at a temperature of 190-210°C, a rotation speed of 400-500rpm, and a kneading time of 20-40min; after kneading, it is molded by an injection molding machine at an injection molding temperature of 160-200°C, a mold room temperature, an injection molding pressure of 500-700bar, and an injection molding time of 10-20s. After the injection molding is completed, the pressure is maintained at 500-70bar, and the swimming pool film is obtained through embossing, cooling, and trimming.

Citation Information

Patent Citations

  • Polyvinyl chloride modified resin

    CN101143954A

  • Polymer-based cerium-doped nano zinc oxide compound antibacterial agent for fabric and preparation method thereof

    CN105648745A

  • Antiskid and antibacterial swimming pool coiled material

    CN113022063A

  • Corrosion-resistant and fire-resistant control cable

    CN113480818A

  • Antioxidant fading-resistant PVC (polyvinyl chloride) swimming pool adhesive film and preparation method thereof

    CN116922899A